AKSES TRANSPORTASI DALAM PENURUNAN BIAYA LOGISTIK KEPULAUAN BERBASIS KOMODITI UNGGULAN LOKAL - Marcus Tukan; Hozairi Hozairi; Billy J. Camerling (ALE Proceeding, 2021)
Smooth access to ships and ports can reduce logistics costs, therefore transportation is seen as the lifeblood of the regional economy. The decrease in logistics costs (B_L) is a function of ship visits (Call) with available loading and unloading capacity (Q_bongkar), unloading performance (K_B/M) is the ability and efficiency of the use of loading and unloading labor (TKBM) at the port including loading and unloading equipment. loading at a port in an area, the efficiency of logisticBL logistics transport costs can improve the transportation performance of the archipelago and this condition will have a derivative impact on the purchasing power of the people in the islands. The results of the study obtained parameters 0 = -1.102, 1 = 0.001046, 2 = 0.00005, 4 = + 08970, 4 = 0.000000 where the increase in logistics costs can affect Call, Q_bongkar, Performance_B/M, GRDP_unggulan, if B_L increases by 1% will have an impact also for all existing parameters. if performance_B/M = + 08970. then B_L has a fairly good correlation with improved loading and unloading performance at the port and has a significant effect on cargo which has a strong impact on price declines in encouraging purchasing power and economic growth